The Impact of Emotional Intelligence on The Performance of Accountants Working in Government Institutions: A Study of The Opinions of a Sample of Accountants and Auditors in Government Institutions - Ibrahim Muhammad Ali; Fadhil Abbas Sultan; Ahmed Mohammed Ali Mohammed Ameen; Aymen Raheem Abdulaali Almayyahi (International Journal on Economics, Finance and Sustainable Development, 2026)
The aim of the study was to establish the effect of emotional intelligence on the performance of the Iraqi accountants in the professional environment. In this regard, the authors have conducted a field survey, which measures the viewpoints of a group of accountants and auditors working in government agencies, and found 210 respondents in total.The search found that there was a statistically significant relationship among the different dimensions of emotional intelligence and quality of performance of accountants. That is, high levels of emotional intelligence in an accountant is a favourable signifier of his or her professional competence and quality of work. Moreover, the paper reported that accountants who have a high level of emotional intelligence are in a better position to manage their feelings, adjust to work stress, and communicate effectively with other employees and clients, a combination of which boosts the accuracy and quality of their accounting services/work. The study therefore suggested that accounting institution should carry out training programs, and professional development schemes towards instilling skills on self-awareness, emotion, empathy, and teamwork. These interventions are likely to enhance the efficiency and performance of accountants at the work place.